2010
DOI: 10.1016/j.jad.2010.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of persistent suicide ideation, plans, and attempts during college

Abstract: Background Suicide is the second-leading cause of death among college students in the US and is preventable. Approximately 1,100 college students die by suicide each year. This study examined the prevalence and predictors of one-time and persistent suicide ideation, plans, and attempts reported during college. Methods Data were gathered prospectively over four years. Face-to-face interviews were conducted with 1,253 first-year college students at one large mid-Atlantic university. Risk factors were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
200
1
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 290 publications
(241 citation statements)
references
References 17 publications
26
200
1
14
Order By: Relevance
“…Our population-based estimate of frequency (2% of the overall sample; 32% of those with a history of SI) is similar to the 3% and 25% of American college students respectively who reported more than one SI episode over four years. 8 Similarly, Zivin et al 12 reported that 35% of college students with suicidal thoughts reported suicidal thoughts two years later. Borges et al 7 reported that 35% of American adults aged 25-65 years reported recurrent SI over ten years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our population-based estimate of frequency (2% of the overall sample; 32% of those with a history of SI) is similar to the 3% and 25% of American college students respectively who reported more than one SI episode over four years. 8 Similarly, Zivin et al 12 reported that 35% of college students with suicidal thoughts reported suicidal thoughts two years later. Borges et al 7 reported that 35% of American adults aged 25-65 years reported recurrent SI over ten years.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Often defined as an indicator of severe emotional distress, suicidal ideation (SI) is one of the most robust predictors of self-harm, suicide attempts and completed suicide. 2,[4][5][6] SI that recurs over time could indicate ongoing severe depression [7][8][9] and may be linked to an increased risk of making suicide plans and suicide attempts. 5,10 However few longitudinal studies investigate recurrent SI in population-based samples 10,11 and in particular among young adults in whom the prevalence may be elevated.…”
mentioning
confidence: 99%
See 3 more Smart Citations